Touch the spirit, Korea - Kum, Ha (Seoul, Korea : Korea National Tourism Organization, 1995)
Presenta ilustraciones relacionadas con la vida y costumbres de Korea, folklore, deporte, lugares de compras, templos, incluye 837 fotos de los más diversos lugares visitados por los turistas en ese país..
Requisitos del sistema for MPC: 486DX or higher, 8MB RAM; 256 colors (SVGA); printer recommended; MS Windows 3.1 or Higher; Soundboard and Speaker, insert the CD-ROM into the drive, from the Program Manager. choose Run from the file menu, in the Command Line box, type d:/Setup.EXE (where d is the letter assigned to you CD-ROM drive). Click on OK, from the Program Manager double-click on the icon in the Korea group. Double-click on the Korea icon Requisitos del sistema para MACINTOSH: CPU 68040 or Higher, 8MB RAM; 13" color monitor (256 colors); System 7.1 or Higher; Printer Recommended; Soundboard and Speaker, inser the CD-ROM into the drive, double-click on the Korea icon
Keywords: COREA DEL SUR -- DESCRIPCIONES Y VIAJES